Interventions in patients with nutritional disorders: Literature Review - Safrudin, M Bachtiar; Nurrahmawati, Alfina; Yusnanda, Bunga; Aldini, Fhauzia Iin (INDOGENIUS, 2025)
Background & Objective: Nutritional disorders are disorders caused by a lack of nutritional needs that cannot be met to maintain body health. This nutritional disorder problem can be caused by diseases that make it difficult to eat so that nutritional disorders can occur. This nutritional disorder occurs in patients with cancer, diabetes and elderly people who are old because of the reduced level of appetite they have. Method: The method used in writing this literature review is to use a comprehensive strategy, such as searching for articles in the research journal database used, keywords used to search for articles, and limitations of the search for articles to be reviewed based on the year of publication of at least the last 5 years, language, and availability in full text form. Result: Interventions that can be given to these patients are feeding through nasogastric and parenteral. Parenteral nutrition is done by administering 10% aminosteril, 20% lipid and NS+KCL+Ca fluid (a mixture of NACL, calcium potassium chloride, and calcium). Conclusion: Various interventions have been identified as solutions to overcome nutritional disorders, including feeding through nasogastric or parenteral, proper diet planning, regular monitoring of patient nutritional status, and health education to patients and their families.